MINAT REMAJA DI DESA PASIE LAWEH KECAMATAN LUBUK ALUNG KABUPATEN PADANG PARIAMAN TERHADAP OLAHRAGA ARUNG JERAM - m rojiun; Donie -; Yendrizal -; Anton Komaini (Universitas Negeri Padang, 2020)
The problem in this research is the alleged lack of interest of youth in Pasie Laweh Village, Lubuk Alung District, Padang Pariaman Regency in white water rafting. This is based on several factors, namely internal factors and external factors. This study aims to see the interest of youth in Pasie Laweh Village, Lubuk Alung Subdistrict, Padang Pariaman Regency on Rafting Sports. The research method used is descriptive research. The population in this study were 1444 people. Sampling using purposive sampling technique by taking 10% of the total population so that the number of samples in this study amounted to 144 people. The data analysis technique used is the percentage analysis technique. The results of the data analysis show that the interest of the youth of Pasie Laweh Village, Lubuk Alung District, Padang Pariaman Regency towards rafting, there are 6 people (4.2%) with very high interest criteria, 40 people (27.8%) with High interest criteria, 61 teenagers (42.4%) with moderate interest criteria for rafting, there were 24 people (16.7%) with Low interest criteria, and there were 13 teenagers (9%) ) with Very Low interest criteria.